2019
DOI: 10.1038/s41593-018-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional monosynaptic tracing for dissecting subtype-specific organization of GABAergic interneuron inputs

Abstract: Functionally and anatomically distinct cortical substructures such as areas or layers contain different principal neuron (PN) subtypes that generate output signals representing particular information. Various types of cortical inhibitory interneurons (INs) differentially but coordinately regulate PN activity. Despite a potential determinant for functional specialization of PN subtypes, the spatial organization of IN subtypes that innervate defined PN subtypes remains unknown. Here we develop a genetic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
(90 reference statements)
1
31
0
Order By: Relevance
“…In the cortex, SSTi are the regulators of principal cell activity offering inhibitory mechanisms through GABAergic innervation that locally regulate dendritic computation (Chiu et al, 2013;Yetman et al, 2019). A reduction of SSTi number in the hippocampus and a consequent loss of inhibition drive to the excitatory input of the granule cells were found in the pilocarpine mice model of epilepsy (Hofmann, Balgooyen, Mattis, Deisseroth, & Buckmaster, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the cortex, SSTi are the regulators of principal cell activity offering inhibitory mechanisms through GABAergic innervation that locally regulate dendritic computation (Chiu et al, 2013;Yetman et al, 2019). A reduction of SSTi number in the hippocampus and a consequent loss of inhibition drive to the excitatory input of the granule cells were found in the pilocarpine mice model of epilepsy (Hofmann, Balgooyen, Mattis, Deisseroth, & Buckmaster, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…6A-C. These begin with current understanding of the most basic circuit elements in V1 (Pfeffer et al, 2013;Pi et al, 2013;Tremblay et al, 2016;Yetman et al, 2019) on which we have superimposed the network dynamics observed in normal conditions (Figs. 1 and 2) and during a variety of optogenetic manipulations .…”
Section: Circuits Determining the Balance Between Depression And Sensmentioning
confidence: 97%
“…We began by investigating the role of PV interneurons which are the most numerous inhibitory subtype and have been shown to modulate the gain of visual responses in PCs (Celio, 1986;Atallah et al, 2012). PV interneurons are also relatively isolated within inhibitory networks of the cortex, making strong and direct connections with PCs but not transmitting significantly to SST or VIP interneurons (Yetman et al, 2019), making it easier to interpret their role in adaptation.…”
Section: Pv Interneurons Drive Depressing Adaptation In Pyramidal Cellsmentioning
confidence: 99%
See 2 more Smart Citations